Ekoteologi Aswaja: Integrasi Nilai-Nilai Nahdlatul Ulama dalam Etika Lingkungan - Firnando, Hero Gefthi; Setiawati, Cucu (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2025)
This research examines the integration of Aswaja values ​​into a conceptual model of Aswaja Ecotheology as a contextual framework for Islamic environmental ethics. The study uses the perspective of Islamic ecotheological theory, specifically Nasr's tauhidic paradigm, which emphasizes the unity of the relationship between God, humans, and nature as the moral and spiritual basis of Islamic ecological ethics. The study employs a Systematic Literature Review (SLR) approach to 592 scientific publications indexed in Scopus, Web of Science, Google Scholar, and Sinta (2015–2025). The results show that Aswaja values ​​can be conceptually integrated into Islamic ecotheology to form an Aswaja Ecotheology model that emphasizes spiritual, social, and ecological balance. Fokus penelitian ini adalah mengkaji integrasi nilai-nilai Aswaja dalam pembentukan model konseptual Ekoteologi Aswaja sebagai kerangka etika lingkungan Islam yang kontekstual. Kajian menggunakan perspektif teori ekoteologi Islam, khususnya tauhidic paradigm Nasr yang menekankan kesatuan hubungan antara Tuhan, manusia, dan alam sebagai dasar moral dan spiritual dalam etika ekologis Islam. Penelitian menggunakan pendekatan Systematic Literature Review (SLR) terhadap 592 publikasi ilmiah terindeks Scopus, Web of Science, Google Scholar, dan Sinta (periode 2015–2025). Hasil penelitian menunjukkan bahwa nilai-nilai Aswaja dapat diintegrasikan secara konseptual ke dalam ekoteologi Islam untuk membentuk model ekoteologi aswaja yang menegaskan keseimbangan spiritual, sosial, dan ekologis.